2012
DOI: 10.1590/s1679-87592012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of chlorophyll-a in the São Vicente estuary

Abstract: A B S T R A C TEstuaries are extremely dynamic environments that are vulnerable to anthropogenic alterations. Thus, monitoring phytoplankton abundances and composition is an essential tool for the prediction of eutrophication and its effects on coastal ecosystems. Phytoplankton biomass, as chlorophyll-a, in the São Vicente estuary (Brazil) varies in response to tidal cycles and seasonal rainfall. Objectives. To present two datasets designed to assess the relationship between chlorophyll-a and changes in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This lack of correlation was also verified in the São Vicente Estuarine Channel, which is connected to Santos Bay as well (Bucci et al, 2012).…”
Section: Time Variability Of Optical Parametersmentioning
confidence: 79%
“…This lack of correlation was also verified in the São Vicente Estuarine Channel, which is connected to Santos Bay as well (Bucci et al, 2012).…”
Section: Time Variability Of Optical Parametersmentioning
confidence: 79%
“…Thus it is to be expected that their relative contributions be reflected in the optical properties of the estuarine plume formed within Santos Bay, which can be identified as distinct types and monitored by remote sensing spectral reflectances. Some studies on the optical properties of the Santos estuary and Santos Bay have discussed the role of spring tides in the resuspension of inorganic sediments and the estuarine input of organic particles and CDOM during neap tides, whereas CDOM optical properties are not good predictors of surface salinity (BUCCI et al, 2012). Other surveys have shown that summer phytoplankton blooms inside the Santos estuarine complex may produce optical dominance of phytoplankton and are modulated by tides (MOSER et al, 2005;BUCCI et al, 2012), wind patterns (MOSER et al, 2012) and fresh water discharges.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the true-color composite (Figure 8a) suggests that the water with low TSM indexes found in the center of the bay were associated with a brownish water color forming a plume from the main estuarine channel towards the bay. This is probably a result of a very high contribution of Colored Dissolved Organic Matter (CDOM), which has been previously reported in this region (BUCCI et al, 2012;FERRARI et al, 2014), and could trace the estuarine discharge. In estuarine plumes, the decrease in TSM, or CDOM, towards offshore is not a simple process of dilution (OUBELKHEIR et al, 2006), particles size and their chemical composition will also change, leading to biogeochemical and optical changes (BUKATA, 2005;BURD;JACKSON, 2009;CHEN et al, 2005;FETTWEIS et al, 2006).…”
Section: Dynamics Of Tsm In Santos Bay and Its Adjacent Estuarine Commentioning
confidence: 54%
“…Since a high precipitation event was registered in the city of São Paulo two days before the neap tide sampling (CPTEC/INPE 2007), outflows from the power plant to the estuary could explain the anomalous data. Unfortunately, no official discharge data from Henry Borden were available for this period; however, the importance of the Henry Border plant in the study area is discussed in BUCCI et al (2012). Regardless the source of freshwater, our results showed a significant estuarine contribution in both September 2007 campaigns.…”
Section: Dynamics Of Tsm In Santos Bay and Its Adjacent Estuarine Commentioning
confidence: 58%
See 1 more Smart Citation